2018
DOI: 10.3329/imcjms.v12i1.35177
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of New Delhi metallo-beta-lactamase producing Acinetobacter baumannii in patients with ventilator associated respiratory tract infection

Abstract: Background and objectives: Ventilator-associated respiratory tract infection (VARTI) is a major cause of morbidity and mortality among the critically ill patients of intensive care units (ICU). Acinetobacter baumannii, an important offending pathogen in VARTI, has been found to be resistant to several antibiotics including carbapenems. The present study was conducted to determine the rate of New Delhi metallo-β-lactamase 1(NDM-1) producing A. baumannii causing VARTI among the patients admitted in an ICU of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Similar findings have been reported by other investigators. 21 Al-Sweih reported that 13.6% Acinetobacter sp. were resistant to tigecycline where rate was higher than the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported by other investigators. 21 Al-Sweih reported that 13.6% Acinetobacter sp. were resistant to tigecycline where rate was higher than the present study.…”
Section: Discussionmentioning
confidence: 99%